2017
DOI: 10.1007/s13402-017-0332-x
|View full text |Cite
|
Sign up to set email alerts
|

Serine peptidase inhibitor Kazal type 1 (SPINK1) as novel downstream effector of the cadherin-17/β-catenin axis in hepatocellular carcinoma

Abstract: Our current data substantiate our knowledge on the role of CDH17 in the biology of HCC and suggest that components of the CDH17/β-catenin axis may serve as therapeutic targets in CDH17 over-expressing HCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“… 30 SPINK-1 is a serine peptidase inhibitor involved in tumorigenesis that has been found upregulated in a number of tumors, including HCC, where it may promote epithelial to mesenchymal transition phenomena. 31 Finally, ITGA2 is a transmembrane receptor for collagens and related proteins that mediates the adhesion of platelets and other cell types to the extracellular matrix and has been shown to be one of the key genes involved in HCC development. 32 In fact, patients with NAFLD and NAFLD-related HCC have increased platelet activation and adhesion within the liver and blockade of platelet activation prevents HCC development in a murine model of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“… 30 SPINK-1 is a serine peptidase inhibitor involved in tumorigenesis that has been found upregulated in a number of tumors, including HCC, where it may promote epithelial to mesenchymal transition phenomena. 31 Finally, ITGA2 is a transmembrane receptor for collagens and related proteins that mediates the adhesion of platelets and other cell types to the extracellular matrix and has been shown to be one of the key genes involved in HCC development. 32 In fact, patients with NAFLD and NAFLD-related HCC have increased platelet activation and adhesion within the liver and blockade of platelet activation prevents HCC development in a murine model of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, accumulating evidence indicates the significance of aberrant enhancer-mediated transcriptional dysregulation in the formation and maintenance of multiple tumors ( 117 , 118 ), including HCC ( 25 ). In the present study, we identified abundant hypomethylated enhancer-associated activated HCC-related genes such as MUC13 ( 119 ), SPINK1 ( 105 ), and KIF2C ( 97 ), plus hypermethylated enhancer-associated repression of known HCC suppressors like DUSP1 ( 80 ) and ADI1 ( 83 ). Additionally, we found aberrant enhancer-associated dysregulation of genes whose functions are uncharacterized in cancer but harbor possibly essential biological functions.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, SPINK1 is significantly upregulated in HCC tissues compared with corresponding nonmalignant tissues ( 25 , 26 ). It also causes the epithelial-mesenchymal transition (EMT) via MEK/ERK pathway ( 27 ) and acts as a downstream effector of the CDH17/β-catenin axis in HCC ( 28 ). By analyzing the GEO database, we found that SPINK1 was upregulated in the HCC tissues; this was further verified using qRT-PCR in 25 paired HCC tumors and adjacent nontumors.…”
Section: Discussionmentioning
confidence: 99%